2001
DOI: 10.1175/1525-7541(2001)002<0469:eraffs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall and Flooding from Supercell Thunderstorms

Abstract: Supercell thunderstorms, the storm systems responsible for most tornadoes, have often been dismissed as flood hazards. The role of supercell thunderstorms as flood agents is examined through analyses of storm systems that occurred in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 17 publications
0
78
0
Order By: Relevance
“…Compared to individual tornado and flash flood events, relatively few studies have examined the meteorology and climatology associated with TORFF events (Rogash and Smith 2000;Smith et al 2001;RR02). RR02 discussed the meteorological characteristics associated with significant tornado events [at least two tornados rated as category 2 events on the Fujita scale (F2) or one F3 tornado] and flash flooding that occurs within 250 km and 3 h of one another from 1992 to 1998, and found that the meteorological setup was largely indicative of typical tornadic environmental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to individual tornado and flash flood events, relatively few studies have examined the meteorology and climatology associated with TORFF events (Rogash and Smith 2000;Smith et al 2001;RR02). RR02 discussed the meteorological characteristics associated with significant tornado events [at least two tornados rated as category 2 events on the Fujita scale (F2) or one F3 tornado] and flash flooding that occurs within 250 km and 3 h of one another from 1992 to 1998, and found that the meteorological setup was largely indicative of typical tornadic environmental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to MCSs, high-precipitation supercells have been observed to produce flash floods Smith et al 2001). Others have shown that extreme precipitation can result from both strongly and weakly forced synoptic systems (MCH79; Heideman and Fritsch 1988;Bradley and Smith 1994), from tropical storms and hurricanes (Davis 2001), and from terrain-forced convection (Petersen et al 1999;Pontrelli et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been fair amount of research on forecasting flash floods and the associated flood producing systems over the last few decades (e.g. Maddox et al 1979;Doswell et al 1996;Smith et al 2001), most ofthis research has been conducted on weather systems outside of Africa. Therefore, it is essential that continued global research is performed on the types of systems that may have a large negative impact on society.…”
Section: Introductionmentioning
confidence: 99%